Fluorinated Benzofuran Derivatives for PET Imaging of β-Amyloid Plaques in Alzheimer's Disease Brains - Cheng, Yan (American Chemical Society, 2010)
[Image: see text] A series of fluorinated benzofuran derivatives as potential tracers for positron emission tomography (PET) targeting β-amyloid plaques in the brains of patients with Alzheimer's disease (AD) were synthesized and evaluated. The derivatives were produced using an intramolecular Wittig reaction. In experiments in vitro, all displayed high affinity for Aβ(1−42) aggregates with K(i) values in the nanomolar range. Radiofluorinated 17, [(18)F]17, in particular labeled β-amyloid plaques in sections of Tg2576 mouse brain and displayed high uptake (5.66% ID/g) at 10 min postinjection, sufficient for PET imaging. In addition, in vivo β-amyloid plaque labeling can be clearly demonstrated with [(18)F]17 in Tg2576 mice. In conclusion, [(18)F]17 may be useful for detecting β-amyloid plaques in patients with AD.